Finite element analyses and proposed strengthening of a reinforced concrete box girder bridge subjected to differential settlement - Mitchell, Caleb (Kansas State University, 2018)
The Kansas Department of Transportation’s (KDOT) Bridge 059-045 is a reinforced concrete box girder bridge constructed in 1965 to connect the rural Shawnee Drive across Interstate 135 near McPhearson, Kansas, in between Salina and Wichita. The bridge was observed, during an annual inspection in 1998, to have experienced some settlement, which was further found to be due to its proximity to a sinkhole. This settlement progressed to noticeable levels in 2012 necessitating a semi-annual elevation profile survey that was consistently conducted by KDOT. In April 2016, KDOT determined that the bridge required a detailed finite element analysis to determine the safety and suitability of the bridge to stay open to traffic. Accordingly, a two-level Finite Element Analysis was performed using RISA 3D and Abaqus to assess the level of distress in the bridge due to the continuous differential settlement as a result of the active sinkhole deep in the soil under the bridge. The force-moment results were taken from the RISA 3D model for further analysis of various structural components that make up the bridge, including the box girder, piers, and piles. The stress distribution results from the Abaqus model were investigated for the same components of the bridge. A strengthening design scheme using near surface mounted fiber reinforced polymer rebar was developed to extend the service life of the bridge.
Keywords: Finite Element Modeling Settlement Fiber Reinforced Polymer; FEM (Finite Element Modeling); FRP (Fiber Reinforced Polymer); Differential Settlement